Portale społecznościowe do wymiany plików a piractwo medialne - Koćwin, Julitta (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
Media piracy of (copyrighted) intellectual property is currently an integral part of mass culture. The digitalization of culture increases the role of the Internet as a means of easy access to cultural content. Many file downloading and sharing websites appear, and providing illicit access to that kind of content becomes lucrative business. This practice gives rise to problems with the profitability of film and music production, book publishing, etc., as well as with remuneration of authors. The comprehensive presentation of research results describes the nature of media piracy and operating principles of the most popular file sharing networks, and also analyzes the effectiveness of anti-piracy measures. The final conclusions point out the extent of the piracy phenomenon and the dim prospects of stopping this practice, especially since current legislation interprets it in different ways.
Keywords: file hosting services; media piracy; sharing; social networks